Cerebral blood flow, metabolism and function during induced hypotension : an animal study comparing esmolol with isoflurane and sodium nitroprusside - Boezaart, André P (Stellenbosch : Stellenbosch University, 2012)
Thesis (Ph. D. in Anesthesiology ) -- University of Stellenbosch, 1999.